Fine structure of convective motions in the solar photosphere - Kostik, R.I. (Кинематика и физика небесных тел, 2005)
The granulation brightnesses and convective velocities in the solar photosphere between the levels of formation of the continuum radiation and the temperature minimum are examined. The properties of the brightness and velocity are analysed in a sixteen-column model. Four sorts of motions are most typical and efficient. In the first two, only the sign of the relative contrast of the material changes, which occurs, on the average, at a height of 270 km. In the last two motions, both the sign of the contrast and the direction of the motions are reversed near ~350 km. The convective motions maintain their column structure throughout the photosphere, right to the temperature minimum.